Revealing agricultural land ownership concentration with cadastral and company network data - Clemens Jänicke; Daniel Müller (Agriculture and Human Values, 2025)
In many high-income countries, agricultural land is highly concentrated in a few hands, but detailed knowledge of ownership structures is limited. We examined land ownership structures and agricultural land concentration for the entire state of Brandenburg, Germany (1.3 million ha), using cadastral and company network data. Our aim was to characterise all landowners, analyse the degree of ownership concentration, and examine the role of the largest landowners in more detail. We found a high fragmentation of ownership among 185,000 different owners. Most of the land was owned by individuals not active in agriculture and only a third of the land was owned by farmers and other agricultural actors. Absentee ownership covered a quarter of the land. Ownership concentration was low to moderate in most regions and reached high levels in only a few areas. The largest owners were public institutions, private investors and nature protection institutions. Areas where public institutions owned a lot of land showed high concentrations, but also some areas where private landowners owned a lot of land. In summary, our analysis provides rare information on the concentration of agricultural land ownership in a large region. Such analysis facilitates better justification and design of policies that regulate agricultural land markets.
Keywords: 630; farmland; land concentration; financialization; investments in land; land tenure